Sosialisme Demokratis Dalam Kebhinekaan Indonesia - Muhammad Zaki; Daffa Rifqi Rafsanzani; Denis Andryan Hutabarat; Bima Hidayah; Denny Oktavina Radianto (LPPM IAI Nasional Laa Roiba Bogor, 2023)
The purpose of writing this journal is to find out how social democracy is implemented in the Indonesian framework. The main principles of social democracy, such as protection of human rights, social welfare, and economic justice, can become the basis for a social democratic view of life in Indonesia. This journal uses a qualitative descriptive approach using content analysis methods and literature studies. The content analysis method is a research method used to identify conclusions from a text. In contrast, literature studies in this research use types and secondary sources of information obtained from research results, posts and reference books that cover topics related to the theme of the journal. Solutions to social democratic problems that are still not fully implemented in Indonesia's diversity Even though Indonesia has adopted social democratic principles in its constitution, there are still many challenges in its implementation. One of the biggest challenges is the limitations in running a fair and equitable system for all levels of society. Keywords: social, Indonesia, democracy